2009
DOI: 10.1021/ja904380q
|View full text |Cite
|
Sign up to set email alerts
|

Isoquinoline Synthesis via Rhodium-Catalyzed Oxidative Cross-Coupling/Cyclization of Aryl Aldimines and Alkynes

Abstract: A general rhodium-catalyzed oxidative coupling reaction between internal alkynes and aryl aldimines is described. This process affords 3,4-disubstituted isoquinolines in good yield and high regioselectivity. Preliminary mechanistic studies suggest that the C-N bond formation arises from the reductive elimination of a rhodium(III) species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(132 citation statements)
references
References 35 publications
5
123
1
3
Order By: Relevance
“…However, the oxidative alkenylation of heteroarenes is named the Moritani-Fujiwara reaction. [8,9] In this regard, different palladium [10][11][12][13] and rhodium catalysts [14][15][16] have already been used to promote the oxidative alkenylation of heteroarenes with a variety of directing groups, namely, imines, [17,18] amines, [19] and carboxylates. [20,21] Rutheniumcatalyst-directed arylation of unactivated C-H bonds with phenols was reported by Ackermann.…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxidative alkenylation of heteroarenes is named the Moritani-Fujiwara reaction. [8,9] In this regard, different palladium [10][11][12][13] and rhodium catalysts [14][15][16] have already been used to promote the oxidative alkenylation of heteroarenes with a variety of directing groups, namely, imines, [17,18] amines, [19] and carboxylates. [20,21] Rutheniumcatalyst-directed arylation of unactivated C-H bonds with phenols was reported by Ackermann.…”
Section: Introductionmentioning
confidence: 99%
“…It is also imperative to develop routes to highly-substituted isoquinolines to fully explore this chemical space, for example, for potential pharmaceutical targets. While recent synthetic efforts have greatly expanded the diversity of isoquinoline motifs available (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), new routes to isoquinolines are still highly desirable, particularly ones with the ability to directly access the isoquinoline moiety in a range of oxidation levels and which do not require highly-specialized starting materials.…”
mentioning
confidence: 99%
“…However, Fagnou and coworkers convincingly demonstrated that most probably the C-N reductive elimination occurs directly from Rh(III), generating isobutene as side product. 35 Scheme 17. Rh-catalyzed synthesis of isoquinolines from tert-butyl imines.…”
Section: (4+2) Annulationsmentioning
confidence: 99%